Unmanned Aerial Vehicle Development, Concerns, and Future In Modern Warfare - Rivaldy Armando Kamal; Stanislaus Riyanta; Lin Yola (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2025)
The development, use, and prospects of unmanned aerial vehicles (UAVs) in contemporary warfare are to be examined in this paper. As it is, this paper collects data from the Google Scholar and Google search engine to form a comprehensive data as to provide facts and thus compile it in a literature review. From early inventions like the Kettering Bug to the present deployment of AI-powered drone swarms, it charts over the evolution of UAVs and emphasizes their increasing strategic significance in combat. The report highlights how UAVs have changed tactical operations, surveillance, and combat strategies through historical analysis, technology assessments, and a case study on the war between Russia and Ukraine. The report also discusses important issues pertaining to moral conundrums, legal frameworks, and counter-drone strategies in reaction to the widespread use of UAV technology. In the end, this study presents insight into how drones, propelled by AI breakthroughs and defense sector innovation, are changing military operations in the future while posing significant strategic and humanitarian issues.